3D Virtual Worlds as Collaborative Communities Enriching Human Endeavours: Innovative Applications in e-Learning - Dreher, Carl; Reiners, Torsten; Dreher, Naomi; Dreher, Heinz (School of Information Systems, Curtin Business School, 2009)
3D Virtual Worlds are potent Digital Ecosystems because the 3D interface simulates real-world environments and the community of users creates a dynamic, real-to-life economy and in-world culture. Some Virtual Worlds such as Second Life empower users to generate in-world content through object building tools and programming languages; indeed the content in Second Life is entirely user-generated. This promotes a rich culture of innovation surrounding this emerging technology that continually develops the capabilities of the 3D Digital Ecosystem. The collaborative culture spans both the 3D in-world environment and 2D ecosystems: for example, Web 2.0 applications such as wikis and blogs facilitate support, discussion, and documentation for user-generated innovations. Innovation in 3D Digital Ecosystems such as Second Life are applied to all domains of human endeavour that exist in the real-world, including recreation, socialisation, commerce, and education. This working paper shares the authors’ professional experience using Second Life in tertiary Information Systems/Science education and describes specific educational applications. This is followed by discussion of the benefits of 3D Digital Ecosystems for education and suggestions for future research, development, and practice.